(untitled) (Международный научный журнал «Инженер», 2026)
The influence of secondary raw materials of zinc production on the properties of rubbers based on SKI-3 and SKMS-30 ARKM-15 rubbers has been studied. The research results showed that when MCOM is introduced into SKI-3-based rubber compounds in the ratio zinc oxide +BCOM 2.5+2.5 and 1.0+4.0, there are practically no changes in the kinetics of vulcanization. When using MCOM individually as part of elastomeric compositions, the optimal vulcanization time is reduced by 1.19 times compared to a rubber compound containing zinc oxide. It can be every metal oxide in the MCOM composition that affects the vulcanization grid by its activity. For mixtures based on SKMS-30 ARKM-15, a similar dependence of the change in the kinetic parameters of vulcanization is observed as for mixtures based on polyisoprene when a combination of activators is introduced in the same proportions. However, with a further increase in the MCOM content in the rubber compound, the optimal vulcanization time is slightly reduced (by 1.07– 1.09 times) and an increase in the vulcanization rate is observed. Based on the results obtained, it was found that the introduction of VSOM into rubber compounds based on SKI-3 and SK(M)S-30 ARKM-15 in combination with zinc oxide in a ratio makes it possible to obtain rubber compounds and vulcanizates that are not inferior in properties to elastomeric compositions containing a traditional zinc oxide activator.